2020
DOI: 10.1186/s12916-020-01775-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk scores for predicting early antiretroviral therapy mortality in sub-Saharan Africa to inform who needs intensification of care: a derivation and external validation cohort study

Abstract: Background Clinical scores to determine early (6-month) antiretroviral therapy (ART) mortality risk have not been developed for sub-Saharan Africa (SSA), home to 70% of people living with HIV. In the absence of validated scores, WHO eligibility criteria (EC) for ART care intensification are CD4 < 200/μL or WHO stage III/IV. Methods We used Botswana XPRES trial data for adult ART enrollees to develop CD4-independent and CD4-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…Studies that reported potential improved efficiency and cost savings with risk triaging attributed such gains to fewer patients requiring further investigation after risk screening [33]; task shifting as less expensive cadres including lay health workers conduct the screening [42,48,56]; targeting post-risk screening care to patient groups with the highest benefit [38,54]; and reduced resources required for patient tracing due to improved yield [41]. Studies that both implemented and developed risk scoring tools further reported potential health system benefits through portability, ease of transferability [37],…”
Section: Health System Effectsmentioning
confidence: 99%
“…Studies that reported potential improved efficiency and cost savings with risk triaging attributed such gains to fewer patients requiring further investigation after risk screening [33]; task shifting as less expensive cadres including lay health workers conduct the screening [42,48,56]; targeting post-risk screening care to patient groups with the highest benefit [38,54]; and reduced resources required for patient tracing due to improved yield [41]. Studies that both implemented and developed risk scoring tools further reported potential health system benefits through portability, ease of transferability [37],…”
Section: Health System Effectsmentioning
confidence: 99%
“…A number of previous efforts have been made to predict risks of poor outcomes among people living with HIV [10][11][12][13][14][15][16]. While several models include basic demographic characteristics such as age and sex and clinical history such as baseline CD4 count to predict risk, the mechanisms driving risk within demographic subgroups at higher risk of disengagement than their age/sex peers remain unclear.…”
Section: Introductionmentioning
confidence: 99%